Stakeholder Strategies and Sustainable Profitability in Islamic Banking: SDGs, Digitalization, and Institutional Logics - Fahamsyah, Mohammad Hatta; Miharja, Muhammad Najamuddin Dwi; Rakhmat, Adriana Syariefur (Perisai : Islamic Banking and Finance Journal, 2026)
This study investigates the impact of stakeholder-oriented strategies, Sustainable Development Goals (SDGs) integration, and digitalization on the profitability of Islamic banks in Indonesia, with Return on Assets (ROA) used as a proxy for financial performance. A quantitative approach is employed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to analyze panel data from 10 Islamic commercial banks over the period 2019–2023. The findings reveal that stakeholder-oriented strategies have a positive and significant effect on profitability. SDGs integration not only enhances financial performance but also functions as a partial mediator in the relationship between stakeholder strategies and profitability. In addition, digitalization acts as a moderating variable that strengthens this relationship, indicating its role as a strategic enabler in improving financial outcomes. These results highlight the importance of integrating sustainability and digital transformation into the strategic management of Islamic banking institutions. From an institutional logics perspective, the findings reflect the alignment of economic, social, and religious dimensions in achieving sustainable profitability. This study contributes to the literature by offering a comprehensive and integrated framework that links stakeholder theory, SDGs, and digitalization within the context of Islamic banking. Keywords: Stakeholder Strategies, Islamic Banking, SDGs, Digitalization, Profitability (ROA), Institutional Logics